The Global Macroeconomic Situation and Policy Implications - Brahmbhatt, Milan (World Bank, Washington, DC, 2012)
This PREM note provides some perspectives on the ongoing financial turmoil and the present complicated situation in the world economy. Two unifying themes can help to organize the discussion. First, the world economy is working its way through the aftershocks of a major global credit boom-and-bust cycle. A second cross-cutting theme is the emergence of developing countries as major players in the world economy. The combination of these trends could, over time, undermine existing structures of international economic cooperation.